1994
DOI: 10.1113/expphysiol.1994.sp003771
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of intrafusal neuromuscular junctions of cat muscle spindles with gallamine

Abstract: SUMMARYThis is a report on the resistance to block of the motor terminals on intrafusal fibres of cat soleus muscle spindles using the drug gallamine triethiodide (Flaxedil). To minimize diffusion barriers and to permit accurate measurements of time courses, rather slow rates of gallamine infusion were used (0-15 mg min-1). The main finding made was that after gallamine infusion, when extrafusal tension had dropped to half, all dynamic fusimotor effects and eight of twenty static effects had fallen to 40 % or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The rocuronium infusion reduced force to an average of 3% MVC, while animal studies with gallamine showed that a fall in extrafusal tension by one-half was accompanied by block of all dynamic and about one-third of static fusimotor effects (47). Furthermore, in whole body experiments in which the effective local concentration of the blocking agent was much lower than with the local infusion used here, the illusory changes in position were in the opposite direction to the direction of attempted contraction (20).…”
Section: Discussionmentioning
confidence: 98%
“…The rocuronium infusion reduced force to an average of 3% MVC, while animal studies with gallamine showed that a fall in extrafusal tension by one-half was accompanied by block of all dynamic and about one-third of static fusimotor effects (47). Furthermore, in whole body experiments in which the effective local concentration of the blocking agent was much lower than with the local infusion used here, the illusory changes in position were in the opposite direction to the direction of attempted contraction (20).…”
Section: Discussionmentioning
confidence: 98%
“…They proposed that this was due to a weakened spindle signal as a result of an intrafusal motor terminal blockade. It is known that when a muscle is deeply paralyzed, sufficient to block motor terminals on both extrafusal and intrafusal fibers, during the recovery period the extrafusal fibers unblock first, with recovery of intrafusal terminals being delayed (365,427). During recovery, in the face of rapidly rising muscle force, the persisting intrafusal paralysis weakens the coactivation of spindles, and the lower level of afferent discharge leads to a reduction in the sense of force.…”
Section: G Emerging Ideasmentioning
confidence: 99%
“…The interpretation preferred by the investigators was that while all extrafusal fibers were blocked by the paralyzing agent, by virtue of their higher blocking threshold, some fusimotor neuromuscular junctions were still functioning. 40 As a result of the attempted contraction there was coactivation of fusimotor neu-rons, leading to an increase in spindle discharge, which was interpreted by the subject as the muscle lengthening. In supplementary experiments, total muscle paralysis abolished the illusion, consistent with an interpretation based on incomplete paralysis.…”
Section: Kinesthesiamentioning
confidence: 99%